The first genome for the Cape Primrose Streptocarpus rexii (Gesneriaceae), a model plant for studying meristem‐driven shoot diversity. (3rd April 2022) - Nishii, Kanae; Hart, Michelle; Kelso, Nathan; Barber, Sadie; Chen, Yun‐Yu; Thomson, Marian; Trivedi, Urmi; Twyford, Alex D.; Möller, Michael
Abstract: Cape Primroses ( Streptocarpus, Gesneriaceae) are an ideal study system for investigating the genetics underlying species diversity in angiosperms. Streptocarpus rexii has served as a model species for plant developmental research for over five decades due to its unusual extended meristem activity present in the leaves. In this study, we sequenced and assembled the complete nuclear, chloroplast, and mitochondrial genomes of S. rexii using Oxford Nanopore Technologies long read sequencing. Two flow cells of PromethION sequencing resulted in 32 billion reads and were sufficient to generate a draft assembly including the chloroplast, mitochondrial and nuclear genomes, spanning 776 Mbp. The final nuclear genome assembly contained 5, 855 contigs, spanning 766 Mbp of the 929‐Mbp haploid genome with an N50 of 3.7 Mbp and an L50 of 57 contigs. Over 70% of the draft genome was identified as repeats. A genome repeat library of Gesneriaceae was generated and used for genome annotation, with a total of 45, 045 genes annotated in the S. rexii genome. Ks plots of the paranomes suggested a recent whole genome duplication event, shared between S. rexii and Primulina huaijiensis . A new chloroplast and mitochondrial genome assembly method, based on contig coverage and identification, was developed, and successfully used to assemble both organellar genomes of S. rexii . This method was developed into a pipeline and proved widely applicable. The nuclear genome of S. rexii and other datasets generated and reported here will be invaluable resources for further research to aid in the identification of genes involved in morphological variation underpinning plant diversification.